The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1186/s12917-015-0483-9
|View full text |Cite
|
Sign up to set email alerts
|

Reduced canine BRCA2 expression levels in mammary gland tumors

Abstract: BackgroundMammary tumors are the most common tumor type in intact female dogs. Recently, the breast cancer 2 early onset (BRCA2) gene was proposed to be associated with tumorigenesis in dogs. The expression level of BRCA2 is important for its DNA repair function in mammalian cells, and its expression level is linked to tumorigenesis in mammary tissue. However, the expression of canine BRCA2 in mammary tumors is unclear.ResultsBRCA2 mRNA levels were compared between seven mammary gland samples and seventeen mam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 29 publications
(32 reference statements)
0
33
0
Order By: Relevance
“…Thus, Yoshikawa et al later investigated the mRNA levels of BRCA2 in canine mammary tumor samples compared to mammary gland samples and found a significantly reduced level in the tumor samples, suggesting that low expression of BRCA2 contributes to mammary tumor development in dogs [23]. In contrast, a study conducted by Ripoli et al did not show a significant difference in BRCA2 gene expression levels in between canine healthy tissue, malignant and benign tumors from fresh frozen samples [34].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Yoshikawa et al later investigated the mRNA levels of BRCA2 in canine mammary tumor samples compared to mammary gland samples and found a significantly reduced level in the tumor samples, suggesting that low expression of BRCA2 contributes to mammary tumor development in dogs [23]. In contrast, a study conducted by Ripoli et al did not show a significant difference in BRCA2 gene expression levels in between canine healthy tissue, malignant and benign tumors from fresh frozen samples [34].…”
Section: Main Textmentioning
confidence: 99%
“…Thus, certain biomarkers of canine mammary tumors have been discovered and investigated in order to improve early detection of the tumors [20]. Among other gene mutations, mutations in the BRCA1/2 genes (Breast Cancer 1 and 2; their protein products are commonly called breast cancer type 1 or 2 susceptibility protein) have been reportedly associated with the development of mammary tumors in dogs [21][22][23]. Apart from being useful as biomarkers, BRCA1/2 have been also investigated as potential treatment targets [24].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to osteosarcoma, which affects large dog breeds, mammary tumors ( Figure 15) tend to occur in the achondroplastic Dachshund and a number of small breeds including the Poodle, Maltese Terrier, Cocker Spaniel, Yorkshire Terrier and the Beagle. Conserved tumorigenesis orthologs implicated in this tumor type include CTNNB1 and PTEN [59] while least conserved orthologs associated with canine mammary tumors include BRCA1 [4] AND [60], BRCA2 [61], MUC1 [62], and KLF4 [63]. Interestingly, tumor associated macrophages (TAMs) have been implicated in modulating tumor invasion and metastasis in this cancer type [64].…”
Section: Discussionmentioning
confidence: 99%
“…It binds to Rad51 recombinase through interaction with eight BRC repeats, and the complex repairs DNA damage through homologous recombination repair ( Figure 4) [72,[78][79][80]. In one study, it was found that mammary tumors express less BRCA2 than normal mammary glands, which would explain how mutations causing breast cancer might arise [72]. However, the cause for the underexpression is unclear-there were no mutations in the promoter that might affect transcription levels.…”
mentioning
confidence: 99%
“…However, the cause for the underexpression is unclear-there were no mutations in the promoter that might affect transcription levels. The study discovered two BRCA2 splice variants, one of which induced a shift in reading frame that lead to nonsense-mediated RNA decay and thus underexpression [72]. In addition, there were many single nucleotide polymorphisms in exon 11 of BRCA2 (Table 7) and a high frequency of genetic variation at two "hot spots" (A511C and A2414G) in many tumors that could have led to BRCA2 underexpression [79,81,82].…”
mentioning
confidence: 99%